Magic Polymer Gel Dosimetry Using X-Ray Computed Tomography: A Feasibility Study - Mohammad Aljamal, Mohammad Abdalla (2008)

(untitled)
Projek ini bertujuan mengkaji kebolehlaksanaan pembangunan sistem dosimetri gel polimer MAGIC ("Methacrylic and Ascorbic acid in Gelatin Initiated by Copper") menggunakan "helical multislice" tomografi berkomputer sinar-X di HUSM untuk menentukan taburan dos. Gel MAGIC disediakan mengikut formula yang telah dicadangkan oleh Fong et ai. (2001) dengan sedikit perubahan. Gel ini dikaji untuk melihat samada ia mempunyai ciri-ciri yang sarna dengan air. Prinsip Archimedes digunakan untuk menentukan kepadatanjisim (P) dan sementara itu pengiraan pecahan berat kandungan elemen dan nombor atomik efektif (Zeff) gel juga dilakukan. The aim of this project is to carry out the feasibility study of developing MAGIC (Methacrylic and Ascorbic acid in Gelatin Initiated by Copper) polymer gel dosimetry system by utilising helical multislice X-ray computed tomography (CT) available in HUSM to determine dose. The MAGIC gel was prepared based on the formulation proposed in the literature by Fong et al. (2001) with some modifications. The characteristics of the gel were studied for its water-equivalent properties. The mass density (P) was determined based on Archimedes' principle.